2004
DOI: 10.1021/la035381j
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization Mechanism of Calcium Phosphates under Three Kinds of Langmuir Monolayers

Abstract: Three kinds of Langmuir monolayers formed by dipalmitoylphosphatidylcholine (DPPC), arachidic acid (AA), and octadecylamine (ODA) were used as templates to study the initial stage of nucleation and crystallization of calcium phosphates. It was demonstrated that the combination of calcium ions (or phosphates) to the monolayer/subphase interface is a prerequisite for subsequent nucleation. It was found that calcium phosphate dihydrate (DPCD) formed at 25.0 degrees C for 12 h has a biphasic structure containing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 51 publications
2
60
1
Order By: Relevance
“…The control titanium sample and the OH-modified sample showed less calcium phosphate deposition than the COOH-and PO 4 H 2 -modified samples [52]. While most of the results so far indicate that negatively charged functional groups are more effective than positive or neutral groups in inducing heterogeneous nucleation of HA [50,53], there are some studies showing different results: Zhang et al [60] investigated HA precipitation in the presence of PO 4 , COOH and NH 2 functional groups present on Langmuir monolayers made of dipalmitoylphosphatidylcholine, arachidic acid and octadecylamine, respectively. They showed that all PO 4 , COOH and NH 2 functional groups promoted the nucleation of calcium phosphate to very similar extents [60].…”
Section: Amino Acids Bound To Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The control titanium sample and the OH-modified sample showed less calcium phosphate deposition than the COOH-and PO 4 H 2 -modified samples [52]. While most of the results so far indicate that negatively charged functional groups are more effective than positive or neutral groups in inducing heterogeneous nucleation of HA [50,53], there are some studies showing different results: Zhang et al [60] investigated HA precipitation in the presence of PO 4 , COOH and NH 2 functional groups present on Langmuir monolayers made of dipalmitoylphosphatidylcholine, arachidic acid and octadecylamine, respectively. They showed that all PO 4 , COOH and NH 2 functional groups promoted the nucleation of calcium phosphate to very similar extents [60].…”
Section: Amino Acids Bound To Surfacesmentioning
confidence: 99%
“…While most of the results so far indicate that negatively charged functional groups are more effective than positive or neutral groups in inducing heterogeneous nucleation of HA [50,53], there are some studies showing different results: Zhang et al [60] investigated HA precipitation in the presence of PO 4 , COOH and NH 2 functional groups present on Langmuir monolayers made of dipalmitoylphosphatidylcholine, arachidic acid and octadecylamine, respectively. They showed that all PO 4 , COOH and NH 2 functional groups promoted the nucleation of calcium phosphate to very similar extents [60]. However, the Ca/P ratio for the calcium phosphates formed in the presence of PO 4 was similar to that of HA (1.67), whereas COOH (1.49) and NH 2 (1.60) showed lower Ca/P ratios indicating the presence of ACP precursor.…”
Section: Amino Acids Bound To Surfacesmentioning
confidence: 99%
“…Most of the works show that HA precipitation was faster on negatively charged than on positively charged SAMs, and that among the negatively charged groups, phosphonate groups are the strongest HA nucleators [23,24]. In one case, though, it was found that PO 4 , COOH and NH 2 functional groups promoted the nucleation of calcium phosphate to a very similar extent [25]. However, the Ca/P ratio for the calcium phosphate formed in the presence of PO 4 was similar to that of HA (1.67) while lower Ca/P ratios were found for COOH (1.49) and NH 2 (1.60), indicating the presence of some amorphous calcium phosphate (ACP) on these samples.…”
Section: Introductionmentioning
confidence: 99%
“…(-NH 3+ ) groups, this organic multilayered template is able to regulate biomineral formation and overcome the dispersion problem of CaP particles on PET fibers (17). In addition, the carboxylic groups interact with the calcium ions of CaP, which enables the multilayered template to effectively stimulate BM and induce the deposition of crystalline CaP (18)(19)(20). However, in contrast to other fast methods for biomimetic deposition of nanocrystalline apatite, the current technique requires approximately three days to deposit a uniform nanoscale CaP coating on the PET ligament, which may be due to the chemical and physical properties of the surface of the PET ligament.…”
Section: Resultsmentioning
confidence: 99%